2002
DOI: 10.1080/00288233.2002.9513507
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and glucose kinetics in sheep fed plantain and orchard grass and exposed to cold

Abstract: To investigate the characteristics of plantain (PL), a forage herb, as a feed for ruminants, chemical components, energy digestibility, rumen constituents, concentrations of blood metabolites (glucose, nonesterified fatty acids, lactate, acetate, and propionate), and insulin were measured in four sheep fed PL and orchard grass (OR), a forage. Net blood glucose turnover rate in response to cold exposure (0-4°C on Day 5) was also determined using an isotope dilution method of [U-13 C]glucose. Dry matter intake w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…Weight change differed little between the diets, and BW tended to be reduced (P = 0.06) during cold exposure. Similar results were observed in sheep fed fresh PL and OR diets (Sano et al 2002). The tendency toward reduced BW during cold exposure may mainly be due to reduced digestibilities and water intake and enhanced energy expenditure (Kennedy et al 1976;Kennedy & Milligan 1978;Tsuda et al 1984) because feed intake was the same in both environments.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Weight change differed little between the diets, and BW tended to be reduced (P = 0.06) during cold exposure. Similar results were observed in sheep fed fresh PL and OR diets (Sano et al 2002). The tendency toward reduced BW during cold exposure may mainly be due to reduced digestibilities and water intake and enhanced energy expenditure (Kennedy et al 1976;Kennedy & Milligan 1978;Tsuda et al 1984) because feed intake was the same in both environments.…”
Section: Resultssupporting
confidence: 80%
“…Of the chemical compositions and macrominerals in the diets, neutral detergent fibre and ether extract were lower for the PL diet, whereas Ca content was considerably greater for the PL diet than for the OR diet (Table 1) as observed previously (Sano et al 2002). Six sheep consumed all the diets which were fed, but the other two sheep could not eat all the OR diet ( Table 2).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…In a previous study, Sano et al (2002) reported that diets containing plantain contained less gross energy than those with orchardgrass. Furthermore, the plasma concentration of NEFA is linearly and negatively correlated with feed intake of ewes (Landau et al, 1992).…”
Section: Discussionmentioning
confidence: 94%
“…It was found that roughage generated a higher heat increment than concentrate (Sudarman and Ito, 2000). Sano et al (2002) stated that plantain showed a more concentrate-like fermentation pattern than orchardgrass hay, which might be partially responsible for this higher rectal temperature. It is well known that, like the present experimental findings, HE increases rectal temperature in sheep.…”
Section: Discussionmentioning
confidence: 99%